Nurses’ and patients’ perceptions of privacy protection behaviours and information provision - Gim, Gyeong hui (Nursing ethics, 2017)
Background:With increased attention to patient privacy and autonomy, privacy protection and information provision for patients are becoming increasingly important.Objectives:The aim of this study was to identify and analyse nurses’ and patients’ perceptions of the importance and performance of protecting patients’ privacy and providing them with relevant information.Research design:This study is a descriptive cross-sectional investigation. Participants and research context: Participants were 168 patients hospitalised in medical and surgical wards and 176 nurses who cared for them.Ethical consideration:This study was approved by the Chung-Ang University Bioethics Committee, and informed written consent was collected from all participants.Findings:Nurses’ recognition of the importance of protecting patients’ privacy and providing adequate information was higher compared to their actual performance, and the nurses’ level of performance was higher in comparison with the patients’ recognition of its importance.Discussion:Although a holistic approach to patient privacy protection and information provision is needed, the medical field has not embraced this model of care.Conclusions:These findings provide empirical data to create an ethical environment for the future, as considerable attention has been devoted to patients’ rights and medical institutions’ liability for providing explanations to patients.